Pathogenic in-Frame Variants in SCN8A: Expanding the Genetic Landscape of SCN8A-Associated Disease - Wong, Jennifer C.; Butler, Kameryn M.; Shapiro, Lindsey; Thelin, Jacquelyn T.; Mattison, Kari A.; Garber, Kathryn B.; Goldenberg, Paula C.; Kubendran, Shobana; Schaefer, G. Bradley; Escayg, Andrew (Frontiers in Pharmacology, 2021)
Numerous SCN8A mutations have been identified, of which, the majority are de novo missense variants. Most mutations result in epileptic encephalopathy; however, some are associated with less severe phenotypes. Mouse models generated by knock-in of human missense SCN8A mutations exhibit seizures and a range of behavioral abnormalities. To date, there are only a few Scn8a mouse models with in-frame deletions or insertions, and notably, none of these mouse lines exhibit increased seizure susceptibility. In the current study, we report the generation and characterization of two Scn8a mouse models (IRL/+ and VIR/+) carrying overlapping in-frame deletions within the voltage sensor of domain 4 (DIVS4). Both mouse lines show increased seizure susceptibility and infrequent spontaneous seizures. We also describe two unrelated patients with the same in-frame SCN8A deletion, highlighting the clinical relevance of this class of mutations.